MULTIMEDIA-ASSISTED DIRECT INSTRUCTION LEARNING MODEL ON STRUCTURES AND FUNCTIONS OF PLANTS TISSUE - HAFNATI RAHMATAN; ROSMALINA ROSMALINA (Sriwijaya University Learning and Education International Conference, 2016)
This research was intended to find out students’ level of understanding on the concept ofstructures and functions of plant tissue through implementation of multimedia-assisteddirect instruction learning model. This study was conducted from June 2014 to February2015. This research was carried out in an experimental, pretest-posttest control groupdesign. The population in this study was students from class XI.IA1 to XI.IA5 inSeniorHigh School1 Bandar Baru, Pidie, Indonesia, with the total of 125 students. The sampleswere determined by purposive sampling technique, and further divided into two classes,namely experimental class (XI.IA1) and control class (XI.IA2) consisting of 24 and 25students. The data was collected by giving test consisting of 50 validated questions. It wasobtained that the t-test value was higher than t-table value (10,81 > 2,01) at level ofsignificance = 0,05. In brief, students’ understanding on the concept of structures andfunctions of plant tissue had been improved through the implementation of multimediaassisteddirect instruction learning model.